Deconstructing Ex Machina (2014): a feminist-psychoanalytic exploration of female artificial intelligences - Dai, Yongde (Frontiers in Communication, 2024)
This article examines the portrayal of female artificial intelligences (AIs) in Hollywood's science fiction (SF) films, with a primary focus on Ex Machina (dir. Alex Garland, 2014). Employing feminist and psychoanalytic perspectives, the study critically reassesses how socio-cultural expectations and patriarchal desires shape the cinematic representation of female AIs. It seeks to address a nuanced gap by revealing the unconscious psychological forces that mold gendered imprints within technology and analyzing how (female) AIs, positioned as posthuman beings, not only mirror but engage in the construction of femininity for the fulfillment of male fantasies and the subversion of male dominance, accomplished through the strategic manipulation of "artificial skin" and gynoid bonding. Finally, this paper aims to contribute to the broader discourse on gender dynamics surrounding female AIs and their power relations with humanity in the cinematic SF. It explores the narrative functions of intelligent fembots, which may disrupt patriarchal narratives both in reel life and, perhaps, real life.